2007
DOI: 10.4081/jlimnol.2007.81
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic characteristics and diversity of freshwater Synechococcus at two depths during different mixing conditions in a deep oligotrophic lake

Abstract: We studied the photosynthetic characteristics and genetic diversity of Synechococcus assemblages at two different light and mixing conditions in a deep oligotrophic lake (Lake Maggiore, Northern Italy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…The study of the photosynthetic characteristics and genetic diversity of Synechococcus populations under various light and mixing conditions showed that samples from different depths and with different nutrient concentrations hosted different strains characterised by different genetic fingerprints and photosynthetic properties [139]. As for the production of organic matter accounted for by the smaller photosynthetic organisms, it was estimated that the annual average productions of autotrophic picoplankton in 1994 and 1998 were 16 and 41 g C m À2 year À1 , which represented a total phototrophic production of between 10 and 20%.…”
Section: Microbial Ecologymentioning
confidence: 99%
“…The study of the photosynthetic characteristics and genetic diversity of Synechococcus populations under various light and mixing conditions showed that samples from different depths and with different nutrient concentrations hosted different strains characterised by different genetic fingerprints and photosynthetic properties [139]. As for the production of organic matter accounted for by the smaller photosynthetic organisms, it was estimated that the annual average productions of autotrophic picoplankton in 1994 and 1998 were 16 and 41 g C m À2 year À1 , which represented a total phototrophic production of between 10 and 20%.…”
Section: Microbial Ecologymentioning
confidence: 99%
“…2) with higher concentrations detected within the first 20 cm . The microbiology of the lake remains a black-box, particularly compared to well characterized microbial communities of other alpine (Callieri et al, 2006) and subalpine lakes in the area (Callieri et al, 2007(Callieri et al, , 2012Bertoni et al, 2010).…”
Section: Lake Orta An Ideal Case Study?mentioning
confidence: 99%
“…Microorganisms capable of photoautotrophy are present in a diverse array of habitats including the ocean, freshwater and soil (Callieri et al ., 2007; Fernández‐Valiente et al ., 2007; Michelou et al ., 2007). While photoautotrophic microbial communities in soil have been characterized (e.g.…”
Section: Introductionmentioning
confidence: 99%